Geriatric Medicine and Healthy Aging (IntechOpen, 2023)
Geriatric Medicine and Healthy Aging supports the idea that living a long and healthy life is considered the foremost challenge of societies worldwide. Promoting healthy aging strategies, which involves enhancing physical, mental, and social well-being in older adults, is discussed throughout the book, considering different approaches. Among a range of practical strategies for promoting healthy aging, physical activity is considered a key recommendation for developing sustainable policies and action programs at the community level. As such, the book discusses how increasing physical activity is necessary to maintain functional and cognitive abilities and social activities in older age. The book also examines assisted living technologies to support healthy aging, giving special attention to innovative information and communications technology (ICT)-based products. Recent evidence shows the transformative power of assisted living technologies in people’s physical, mental, and social lives. By the end of this book, readers will have a solid grasp of the relationship between healthy aging, physical activity, functional fitness, cognitive function, and assisted living technologies. They will understand how these concepts function as vital structural elements for the sustainability of health and the enhancement of quality of life in older people.